2020
DOI: 10.1111/eip.13029
|View full text |Cite
|
Sign up to set email alerts
|

The effects of patient personality traits and family cohesion on the treatment delay for patients with first‐episode schizophrenia spectrum disorder

Abstract: Aim: The duration of untreated psychosis (DUP) is an important prognostic indicator of schizophrenia. We explored the effects of patient personality and family relationships on delayed schizophrenia treatment.Methods: We prospectively included data from 169 patients diagnosed with firstepisode schizophrenia. Personality traits were investigated using the Big Five Inventory (BFI-10) and family relationship was assessed employing the Family Adaptability and Cohesion Evaluation Scale-III (FACES-III). We explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
1
8
1
Order By: Relevance
“…It was noted in this study that the neuroticism and openness of college students were also strong early warning signs for suicide risk. The results were different among different groups in other studies (Heisel et al, 2006;Bluml et al, 2013;Jo et al, 2021). People with a neurotic personality are generally Openness, as a strong early warning sign of suicide risk in college students, also differed among different groups.…”
Section: Discussioncontrasting
confidence: 62%
“…It was noted in this study that the neuroticism and openness of college students were also strong early warning signs for suicide risk. The results were different among different groups in other studies (Heisel et al, 2006;Bluml et al, 2013;Jo et al, 2021). People with a neurotic personality are generally Openness, as a strong early warning sign of suicide risk in college students, also differed among different groups.…”
Section: Discussioncontrasting
confidence: 62%
“…However, the DUP tends to be relatively long and treatment delays are more common in Korea compared with Western countries. 24 Our results show steady increases in the numbers of treated patients in their 20s and under, which suggests a potential improvement in public awareness in Korea of the need for early treatment of schizophrenia. 8,9 Further studies should investigate the association between DUP and increasing hospital utilization in young patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 52%
“…Usually, family members had persuaded the affected youth to seek help. Our previous research revealed that a long DUP was significantly associated with poorer family cohesion in patients with first‐episode psychosis (Jo et al, 2020 ). Further, strongly expressed emotions are well‐known to be closely associated with relapses and poor outcomes among patients with schizophrenia.…”
Section: Resultsmentioning
confidence: 97%